2018
DOI: 10.1002/dta.2524
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bemitil and its metabolite in urine by means of LC–MS/MS in view of doping control analysis

Abstract: 2-(Ethylthio) benzimidazole is an active ingredient of Antihot, a dietary supplement sold in Ukraine. The substance, available also under names of Bemitil, Metaprot, and Bemaktor, was developed in the USSR in 1970s, and after tests on Soviet cosmonauts and soldiers, several studies on its influence on athletes' performances were conducted. The research showed that bemitil is a synthetic adaptogen which is capable to significantly increase physical performance and reduce the time of regeneration.Moreover, accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…According to the manufacturer, bemitil is known to improve both physical performance and resistance to stress 25 . Therefore, WADA decided to include the compound in its 2018 monitoring program 26 .…”
Section: Resultsmentioning
confidence: 99%
“…According to the manufacturer, bemitil is known to improve both physical performance and resistance to stress 25 . Therefore, WADA decided to include the compound in its 2018 monitoring program 26 .…”
Section: Resultsmentioning
confidence: 99%
“…The substance was put on the WADA Monitoring List in 2019. We could not find any data regarding positive bemethyl tests, probably because methods to detect it in biological fluids were developed only recently (67). Hence, it is not possible to argue that bemethyl is widely used.…”
Section: Bemethylmentioning
confidence: 90%
“…For nicotine, dissenting study results concerning the drug's ergogenic properties were reported, with one investigation showing an increase in exercise performance in time‐to‐exhaustion tests, while another study did not confirm effects on the participating athletes’ performance in a 1 hour time trial experiment, presumably attributable to study design differences. Also, analyses concerning potential patterns of misuse regarding corticosteroids and any combination of beta‐2 agonists were pursued, and the monitoring of 2‐ethylsulfanyl‐1H‐benzimidazole (bemitil) was extended for at least another year, taking into account the recommendation of including bemitil glucuronide as a target analyte, determined in samples collected in the events of both in‐ and out‐of‐competition.…”
Section: Introductionmentioning
confidence: 99%